2010
DOI: 10.1016/j.ccr.2009.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 Kinase Activity Is Required for the Self-Renewal of Mammary Stem and Progenitor Cells that Are Targets of MMTV-ErbB2 Tumorigenesis

Abstract: Summary Transplantation studies have demonstrated the existence of mammary progenitor cells with the ability to self-renew and regenerate a functional mammary gland. Although these progenitors are the likely targets for oncogenic transformation, correlating progenitor populations with certain oncogenic stimuli has been difficult. Cyclin D1 is required for lobuloalveolar development during pregnancy and lactation as well as MMTV-ErbB2- but not MMTV-Wnt1-mediated tumorigenesis. Using a kinase deficient cyclin D1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
124
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 36 publications
7
124
2
Order By: Relevance
“…MRK-003 similarly altered the differentiation of tumor cells, which normally express only luminallineage markers. Recent findings reveal that luminal progenitor cells may be the cells of origin of the Neuinduced tumors in the Neu (N202) transgenic strain (Jeselsohn et al, 2010). The effect of MRK-003 on mammary epithelial progenitor cell and tumor cell differentiation is consistent with an effect on Notch signaling; numerous studies have demonstrated that this pathway commits normal human and mouse mammary epithelial progenitor cells to the luminal fate and suppresses their differentiation toward the myoepithelial lineage (Buono et al, 2006;Bouras et al, 2008;Raouf et al, 2008;Yalcin-Ozuysal et al, 2010).…”
Section: Mrk-003 Shrinks and Eliminates Tumors In Micementioning
confidence: 83%
“…MRK-003 similarly altered the differentiation of tumor cells, which normally express only luminallineage markers. Recent findings reveal that luminal progenitor cells may be the cells of origin of the Neuinduced tumors in the Neu (N202) transgenic strain (Jeselsohn et al, 2010). The effect of MRK-003 on mammary epithelial progenitor cell and tumor cell differentiation is consistent with an effect on Notch signaling; numerous studies have demonstrated that this pathway commits normal human and mouse mammary epithelial progenitor cells to the luminal fate and suppresses their differentiation toward the myoepithelial lineage (Buono et al, 2006;Bouras et al, 2008;Raouf et al, 2008;Yalcin-Ozuysal et al, 2010).…”
Section: Mrk-003 Shrinks and Eliminates Tumors In Micementioning
confidence: 83%
“…Consistently, PI-MECs can be found in both the basal and the luminal sorted compartments. 33,51,56 In addition, we cannot exclude the possibility that TAp63, alone or as a supporting factor, contributes to epithelial survival during involution. Indeed, TAp63 is localized in the luminal cells, 13,21 which are known to contain PI-MECs and some other mammary progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one of the identified DNp63 target genes, integrin a6 (CD49f), is highly expressed in PI-MECs. 51,56 The study by Carroll et al 35 also highlights the crosstalk between p63-dependent cell adhesion and apoptosis. Specifically, on DNp63 knockdown MCF10A cells exhibit detachment and cell death via anoikis and apoptosis, whereas re-expression of integrin b4 partially rescues both cell adhesion and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations